Examining U.S. grain marketing and farm supply cooperatives' sustainable growth rates. Issue 4 (12th April 2019) - Smart, Nathan; Briggeman, Brian C.; Tack, Jesse; Perry, Edward
Abstract: A challenge for many U.S. grain marketing and farm supply cooperatives is ensuring that exceptional growth rates are sustainable in the long run. Growing too rapidly can sacrifice financial soundness, causing a business to effectively grow broke. The objective of this study is to examine whether or not U.S. grain marketing and farm supply cooperatives are able to manage their recent growth. To do so, we apply the sustainable growth rate (SGR) and sustainable growth challenge (SGC) metrics to a unique panel data set of United States cooperatives. Examining the SGRs for these cooperatives suggests that positive net profit margins are key to positive growth. When actual growth exceeds sustainable growth, most cooperatives are able to rapidly alleviate this difference through increasing leverage or operational efficiency. However, some cooperatives face more persistent growth challenges and are thus the most at risk of growing broke. Large cooperatives and cooperatives more dependent on farm supply sales rely heavily on leverage for managing growth.